Educational Opportunity for Showing Market Animals by Breed - Travis Arp; Chad Carr; Warren Beeler (EDIS)
AN250, a 5-page illustrated fact sheet by Travis Arp, Chad Carr, and Warren Beeler, discusses the ongoing importance of junior livestock shows for the educational value and leadership opportunities they provide, and the challenges that need to be considered for continuing relevance. Includes references. Published by the UF Department of Animal Sciences, August 2010.